Bovine noroviruses: A missing component of calf diarrhoea diagnosis. (January 2016) - Di Felice, Elisabetta; Mauroy, Axel; Pozzo, Fabiana Dal; Thiry, Damien; Ceci, Chiara; Di Martino, Barbara; Marsilio, Fulvio; Thiry, Etienne
Highlights: The most frequent strains of bovine noroviruses (Genus Norovirus, Family Caliciviridae ) belong to genotype 2. Bovine noroviruses have been detected on all continents in both diarrhoeic and non-diarrhoeic calves. Recombination has been detected among bovine noroviruses and appears to contribute to their genetic evolution. Diagnosis of bovine norovirus infection mainly relies on molecular methods. Bovine noroviruses should be considered in the differential diagnosis of calf diarrhoea. Abstract: Noroviruses are RNA viruses that belong to the Genus Norovirus, Family Caliciviridae, and infect human beings and several animal species, including cattle. Bovine norovirus infections have been detected in cattle of a range of different ages throughout the world. Currently there is no suitable cell culture system for these viruses and information on their pathogenesis is limited. Molecular and serological tests have been developed, but are complicated by the high genetic and antigenic diversity of bovine noroviruses. Bovine noroviruses can be detected frequently in faecal samples of diarrhoeic calves, either alone or in association with other common enteric pathogens, suggesting a role for these viruses in the aetiology of calf enteritis.